2008
DOI: 10.1111/j.1469-7610.2007.01845.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological problems in children with cerebral palsy: a cross‐sectional European study

Abstract: A significant proportion of children with cerebral palsy have psychological symptoms or social impairment sufficiently severe to warrant referral to specialist services. Care must be taken in the assessment and management of children with cerebral palsy to ensure psychological problems are not overlooked and potentially preventable risk factors like pain are treated effectively. The validity of the SDQ for children with severe disability warrants further assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
157
6
21

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(201 citation statements)
references
References 43 publications
(72 reference statements)
17
157
6
21
Order By: Relevance
“…With regard to age, Sipal et al (2010) reported lower prevalence estimates for older children with Cerebral Palsy. In contrast, other investigations revealed that age was not related to behavioral problems (e.g., Parkes et al, 2008). Because of these inconsistencies in the literature, the second aim was to investigate whether behavioral problems in children with MID are related to sex and age.…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…With regard to age, Sipal et al (2010) reported lower prevalence estimates for older children with Cerebral Palsy. In contrast, other investigations revealed that age was not related to behavioral problems (e.g., Parkes et al, 2008). Because of these inconsistencies in the literature, the second aim was to investigate whether behavioral problems in children with MID are related to sex and age.…”
mentioning
confidence: 96%
“…Studies using the CBCL reported prevalence rates ranged from 21% (Hendriks, De Moor, Oud, Franken, & Savelberg, 2001), 24% (Peters, Huisman, & Van Emmerik-Levelt, 1999), 30% (Sniekers et al, 2002) to 65% (Sigurdardottir et al, 2010). Using the SDQ, prevalence rates among children with Cerebral Palsy ranged from 26% to 40% (Brossard-Racine et al, 2012;Parkes et al, 2008). Accordingly, the types of behavioral problems in children with motor disabilities also varied.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the study of developmental specificities in pediatric populations has suggested that internalizing problems are more common in older children, and that gender differences in externalizing problems tend to emerge earlier than gender differences in internalizing problems (Pinquart & Shen, 2011). As regards pediatric CP in particular, psychological problems seem frequent and include peer difficulties, inattentionhyperactivity, emotional symptoms, increased dependence, withdrawal, obstinacy and antisocial characteristics (Brossard-Racine et al, 2012a;Parkes et al, 2008). In fact, children and adolescents with CP have been reported to achieve less psychosocial adjustment (Vles et al, 2012), besides being five times more likely to present parent-reported behavior problems than their healthy peers (McDermott et al, 1996).…”
Section: Introductionmentioning
confidence: 99%